Aquatic Oligochaeta (Annelida: Clitellata) Assemblages in the Streams of Biga Peninsula (Marmara-Turkey) and Their Seasonal Variations - Serpil ODABAŞI; Semra CİRİK; Naime ARSLAN (Çanakkale Onsekiz Mart University Journal of Marine Sciences and Fisheries, 2018)
In the present study, aquatic Oligochaeta (Annelida: Clitellata) fauna and environmental parameters from 15 predetermined stations in Sarıçay, Karamenderes, Tuzla, and Kocabaş streams in Biga Peninsula (NorthWest Anatolia) were seasonally studied. Benthic samplings were collected via Hess Sampler and Ekman Birge Grab. During benthic samplings, temperature, electrical conductivity, pH, and dissolved oxygen were analysed on-site whereas chemical oxygen demand (COD), biological oxygen demand (BOD5), and water quality parameters such as PO4-P, and NO3-N were analysed in laboratory. In this study, a total of 340.993 individuals of Oligochaeta belonging 33 different taxawere obtained. The family Naididae had the highest number of species (29 taxa); and followed by Enchytraeidae (2 taxa) and Lumbriculidae (2 taxa).It was demonstrated through Multidimensional Scaling (MDS) that species that are tolerant to organic pollution, including Potamothrix hammoniensis (Michaelsen, 1901), Tubifex tubifex Müller, 1774, Limnodrilus hoffmeisteri Claparede, 1862 are dominant in the stations located in sub tributary basins. In addition, Bothrioneurum vejdovskyanum Stolc, 1886, Mesenchytraeus sanguineus Nielsen & Christensen, 1959 and Enchytraeus christenseni Dozsa-Farkas, 1992, found in this study, are recorded for the first time for the aquatic Oligochaeta Fauna in Turkey.